2018
DOI: 10.1111/jgh.13998
|View full text |Cite|
|
Sign up to set email alerts
|

Searching for a definition for pharmacologically refractory constipation: A systematic review

Abstract: There is need for a detailed definition of pharmacologically refractory constipation before submitting patients to invasive treatments and to evaluate new pharmacological agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Second, inter‐study variability and the symptom‐based approach used in the diagnosis of IBS and PTSD (e.g., Rome IV criteria and the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders) could affect the reliability of current findings. As several of the studies used a self‐report symptom questionnaire in the diagnosis of IBS, there is a known wide variability and ambiguity in each individual's definition of constipation and diarrhea . Furthermore, two of the largest studies included in the meta‐analysis used International Classification of Diseases, Ninth Revision, Clinical Modification code diagnoses based on administrative health records, which are subject to error or misclassification/misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, inter‐study variability and the symptom‐based approach used in the diagnosis of IBS and PTSD (e.g., Rome IV criteria and the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders) could affect the reliability of current findings. As several of the studies used a self‐report symptom questionnaire in the diagnosis of IBS, there is a known wide variability and ambiguity in each individual's definition of constipation and diarrhea . Furthermore, two of the largest studies included in the meta‐analysis used International Classification of Diseases, Ninth Revision, Clinical Modification code diagnoses based on administrative health records, which are subject to error or misclassification/misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that probiotics may alleviate the unwanted constipation [17, 21], weight gain, and adverse metabolic effects [22] commonly associated with antipsychotic use. In the study by Tomasik et al [19], probiotic supplementation was found to significantly increase brain-derived neurotrophic factor (BDNF) levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a complex and likely multifactorial disease like IBS, a multimodal approach is necessary as each agent tends to target individual symptoms, for example abdominal bloating or pain, diarrhoea or constipation . Furthermore, cost concerns exist as repeated courses of treatment are required as IBS is often a chronic, relapsing condition …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…6 In a complex and likely multifactorial disease like IBS, a multimodal approach is necessary as each agent tends to target individual symptoms, for example abdominal bloating or pain, diarrhoea or constipation. 7,8 Furthermore, cost concerns exist as repeated courses of treatment are required as IBS is often a chronic, relapsing condition. 9 Melatonin, N-acetyl-5-methoxytryptamine, is a hormone produced naturally by the pineal gland in humans, as well as the enterochromaffin cells of the gastrointestinal mucosa.…”
mentioning
confidence: 99%